Respuesta :

znk

Answer:

[tex]\large \boxed{8 \times 10^{9} \text{ J}}[/tex]

Explanation:

[tex]\begin{array}{rcl}KE_{2} - KE_{1}&=&\int_{x_{1}}^{ x_{2}}F(x)dx\\KE_{2}- 2.7 \times 10^{11}&=&\int_{0}^{ 7.5 \times 10^{4}}(-3.5 \times 10^{6})dx\\&=&-3.5 \times 10^{6}\int_{0}^{ 7.5 \times 10^{4}}dx\\&=&-3.5 \times 10^{6}(7.5 \times 10^{4})\\& = & -2.62 \times 10^{11}\\KE_{2} & = & 2.7 \times 10^{11} - 2.62 \times 10^{11}\\& = & 0.08 \times 10^{11}\\& = & \mathbf{8 \times 10^{9}} \textbf{ J}\\\end{array}\\[/tex]

[tex]\text{The final kinetic energy of the supply spacecraft would have been $\large \boxed{\mathbf{8 \times 10^{9}} \textbf{ J}}$}[/tex]

As per the evaluation of the kinetic energy of the supply space craft the actual tractors of the beam of light is

F(x)=αx3+β .

  • To find the variation of kinetic energy, let's use the work energy theorem

            W = ΔK            ∫ F .dx = K -K₀

  • If the body starts from rest K₀ = 0            ∫ F dx cos θ = K Since the force and displacement are in the same direction, the angle is zero, so the cosine is 1 we substitute  and integrate.

Learn more about the energy of the supply spacecraft for the actual.

brainly.com/question/17306263.

ACCESS MORE